IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBELAJARAN TEKNIK MEKATRONIKA DI ERA INDUSTRI 4.0 - Agung Lasono Saputra; Erlangga Hikmah Budhyatma (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The Industry 4.0 era introduces challenges such as massive automation and intense competition, which risk triggering individualistic behaviors and a decline in empathy among engineering students. This study aims to analyze the phenomenon of individualism explicitly finding that concerns regarding widespread individualistic attitudes are unfounded and formulate strategies for implementing Pancasila values within the Mechatronics Engineering learning process. The research method employed is a descriptive qualitative method. Data collection was carried out through the observation of laboratory activities, curriculum documentation studies, and in-depth interviews with active students as the primary informants. The results indicate that apathetic behavior among students in classes and laboratories is considerably low due to the implementation of Project-Based Learning methods. Group assignments in complex practical sessions, such as PLC programming and three-phase electric motor installation, naturally compel students to interact and implement the values of mutual cooperation (gotong royong), which reflects the Third Principle. Furthermore, the internalization of Pancasila values and empathy (Second Principle) manifests organically through social solidarity outside of lecture hours, such as peer-to-peer learning initiatives, informal social gatherings, and attending seniors' graduation ceremonies. The study concludes that the integration of structured group assignments combined with independent social solidarity effectively serves as a national character bulwark to mitigate the adverse impacts of digital-era competition.